PENGEMBANGAN MEDIA FLASHCARD BERBASIS DIGITAL MATERI TOKOH-TOKOH PERUMUS PANCASILA UNTUK SISWA KELAS II SEKOLAH DASAR - Tia Salsabila; Syarip Hidayat; Asep Nuryadin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop a digital-based flashcard media for the topic of the founders of Pancasila, targeted at second-grade elementary scholl student. The research method used was Education Design Research (EDR) which includes three stages: exploration, design and contruction, and evaluation and reflection. Validation result from content, pedagogical, and media experts showed an average feasibility score of 94,44% (high feasible). Student responses indicated that 94,87% rated the media as highly feasible, and the teacher gave positive feedback. The digital flashcard media was proven to be appropriate and effective in enhacing student’s understanding and enjoyable way.